Ecofeminism 5.0 - Anurogo, Dito (Universitas Muhammadiyah Surakarta, 2023)
Ecofeminism is a political and social movement that emphasizes the link between women's oppression and environmental degradation. This viewpoint asserts that patriarchal structures and the dominance of nature are intrinsically intertwined and that the liberation of women and the environment must come simultaneously. While ecofeminism presents an important critique of current society, it is not the only lens through which to evaluate the relationship between environmental degradation and social justice.